The Urgency of Implementing the Insolvency Test in Bankruptcy Cases in Indonesia - Lembang , Nisrawanty; Anwar, Iryana (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2025)
The process of resolving bankruptcy cases in Indonesia, which only determines two simple requirements for debtors to be declared bankrupt as stipulated in the provisions of Article 2 paragraph (1) of Law No. 37 of 2004, has resulted in many cases of debtors still in a solvent state but declared bankrupt. This research focuses on the urgency of applying the insolvency test to bankruptcy cases in Indonesia, with the aim of knowing how the urgency of applying the insolvency test in Indonesia, and also knowing how judges apply the concept of the insolvency test even though the insolvency test has not been regulated in the bankruptcy provisions in Indonesia. Normative research using a conceptual approach, and a case approach results in a conclusion that the bankruptcy of a debtor who is still solvent is something that is not in accordance with the principles of bankruptcy. Therefore, it is necessary to have an insolvency test instrument to assess the solvency of the debtor. In addition, this research also found several cases where the panel of judges applied the concept of insolvency test in considering the case being handled.